Sensitive periods to train general motor abilities in children and adolescents: do they exist? A critical appraisal - van Hooren, B.; Croix, M. D. S. (Strength and Conditioning Journal, 2020)
Some long-term athlete development models have proposed generic sensitive periods or "windows of opportunity" during childhood and adolescence that are optimal for training general motor abilities such as strength or speed. However, it remains unclear whether these periods exist. This review will therefore critically appraise the rationale behind generic sensitive periods. We discuss several issues with generic sensitive periods and argue that general motor abilities and the associated sensitive periods do not exist. The identified issues with generic sensitive periods question their validity and we therefore suggest that they should not be used to train youth athletes.